Equity and Outcome Events in Hidradenitis Suppurativa: Exploring Effect Modifiers Associated with Diagnostic Delay in the Real World - Nicole Murray; Isabel Truman; Gary Milligan; Himanshu Modi; Nicholas Adlard (Adis, Springer Healthcare, 2024)
Abstract Introduction Patients with hidradenitis suppurativa (HS) experience significantly delayed diagnoses of 7-10 years from symptom onset on average, but the reasons for this remain largely unknown. This study investigated drivers of diagnostic delay from the perspective of healthcare system equity. Methods A literature review was performed to identify published factors associated with delayed HS diagnosis to inform data analysis. Clinical and demographic data from the Adelphi HS Disease Specific Programme (DSP)™, a real-world cross-sectional survey of dermatologists and their consulting patients in France, Germany, Italy, Spain, the UK and the USA in 2020/2021, were used to model factors influencing delay to diagnosis from onset of symptoms and first consultation. Results Factors influencing delay to HS diagnosis in the literature with the most available evidence were misdiagnosis, delay in specialist referral and patient embarrassment. Data analysis revealed that increasing age was associated with reduced diagnostic delay after symptom onset. Patients with HS who were White or in Germany were also more likely to receive a faster diagnosis. Smokers, patients with concomitant conditions, or a family history of HS were slower to be diagnosed. When time to diagnosis following first consultation was assessed, increasing age was associated with quicker diagnosis. Moreover, patients with a family history of HS were diagnosed quicker, whereas those with high body mass index, more concomitant conditions, in employment, managed by multiple physicians or European were more delayed. Conclusion On the basis of a thorough analysis of real-world data, multiple factors that potentially influenced the timely diagnosis of HS have been identified. For the first time, this study quantifies the relative impact of these modifiers, providing valuable insights into areas that require attention for faster diagnoses and improved disease outcomes. Graphical Abstract